2020
DOI: 10.1038/s41598-020-64658-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Curing on Micro-Physical Performance of Polypropylene Fiber Reinforced and Silica Fume stabilized Expansive Soil Under Freezing Thawing Cycles

Abstract: This study presents the micro-physical investigation of polypropylene (PP) fiber-reinforced, and silica fume (SF) stabilized expansive soil (BC) subgrade. The coupling effect of soil, PP fiber, and SF has been evaluated under the freezing-thawing (F-T) cycle to assess the durability of treated BC Soil. The curing method and duration staggeringly influence the strength of SF treated BC soil; therefore, three different curing method, i.e., moisture-controlled curing (MC), gunny bag curing (GC), and water submerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(17 citation statements)
references
References 85 publications
0
17
0
Order By: Relevance
“…The swelling pressure, expansion percentage, and time rate of swell decrease, whereas the unconfined compressive strength (UCS) increases with the addition of expanded polystyrene (EPS) to soils [22]. Silica fume (SF) and polypropylene (PP) have been shown to be effective at reinforcing soils and show promise in environmentally friendly road work applications [23]. Almajed et al [24] investigated the optimal levels of reinforcement fiber length (FL), fiber dosage (FD), and curing time (CT) for geotechnical parameters of stabilized soil and pointed optimal values of these indicators.…”
Section: Introductionmentioning
confidence: 99%
“…The swelling pressure, expansion percentage, and time rate of swell decrease, whereas the unconfined compressive strength (UCS) increases with the addition of expanded polystyrene (EPS) to soils [22]. Silica fume (SF) and polypropylene (PP) have been shown to be effective at reinforcing soils and show promise in environmentally friendly road work applications [23]. Almajed et al [24] investigated the optimal levels of reinforcement fiber length (FL), fiber dosage (FD), and curing time (CT) for geotechnical parameters of stabilized soil and pointed optimal values of these indicators.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the MICP method has gained popularity for its potential to reinforce soil particles [5][6][7] in comparison with other ground-improvement practices, which use industrial waste, ashes, agricultural waste, and fibers [8][9][10][11][12]. It is one of the environmentally friendly methods for soil improvement [13].…”
Section: Introductionmentioning
confidence: 99%
“…The polypropylene fiber made up of waste plastic has been effectively used as reinforcement 47 51 . Tiwari et al 52 investigated the effect of polypropylene fibers on the reinforcement of the expansive subgrades stabilized with silica fume and found a significant improvement in the engineering properties under freeze-thaw cycles. Deng et al 53 studied the effect of polypropylene fiber to reinforced the expansive subgrades and found that the strength has been increased with the increase of fiber length at optimum moisture content.…”
Section: Introductionmentioning
confidence: 99%